Upaya guru bimbingan konseling dalam mengembangkan kreativitas siswa di MTs Negeri 3 Klaten - Alfian Dewan Adhayuda Prabowo (Universitas Muhammadiyah Ponorogo, 2020)
This study aims to describe the efforts of counseling guidance teachers in developing student creativity in MTs N 3 Klaten. This research uses a qualitative approach with descriptive type. The subjects of the study were two MTs N 3 Klaten counseling guidance teachers. Data collection is done through interviews, observations, and documentation which are analyzed with qualitative data analysis. The results of this study indicate that the counseling guidance efforts of teachers in developing student creativity in MTs N 3 Klaten is by the group guidance method. In the group guidance method there are techniques used including, group discussion, problem solving, role techniques, and games techniques.